An Analysis of the Competitive Situation on the EU Rating Market in Context of Regulatory Requirements - Gunther Meeh-Bunse; Stefan Schomaker (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The market for external ratings is dominated worldwide as well as in the European Union (EU) by three major credit rating agencies (CRAs). These "Big Three" are Standard & Poor's (S&P), Moody's and Fitch Ratings. Due to the oligopolistic market structure and possible involvement in the 2008 financial crisis, the rating agencies have constantly come under criticism. This was associated with stricter regulatory requirements to ease the situation. The EU-Regulation on credit rating agencies ("CRA-Regulation") coming into force 2009 and its amendments in 2011 and in 2013 have mainly governed such regulation. The aim of the article is to analyse potential regulatory impact on the still inherent oligopolistic situation on the EU rating market in the context of the CRA-Regulation. Selected key figures are used to observe over a defined period of time if and how the dominance has changed. The motivation for this article is the observation, that political and private efforts to establish a European rating agency as a counterweight to the three major agencies and other approaches to increase competition in the rating market, followed, which has not been resounding to date. In summary, it is shown that new agencies have a potential impact on the EU rating market and that the three major rating agencies still dominate the market but within a changed environment.
Keywords: G24; G28; 330; Credit rating agencies (CRAs); ratings; regulation; EU-Regulation; corporate finance; capital markets